Technology license agreements as public–private partnerships for economic development: evaluations using surveys, input–output modeling, and regression analysis - Eric D. Raile; Eric K. Austin; Michael P. Wallner; Jeffrey Peterson; Brian Lewandowski; Derek Kapps; Bridger Sellegren; Joe Hutton (Journal of Innovation and Entrepreneurship)
Abstract We evaluate license agreements as a form of technology transfer that constitutes a public–private partnership (PPP) with the primary goal of economic development. These license agreements permit entrepreneurs and other businesses to turn government innovations into earnings. We constructed a complete database of all license agreements between the U.S. Department of Defense and private industry from 2000 to 2021. We first surveyed the companies involved, achieving a 96% response rate. The subsequently anonymized responses allowed us to generate sales numbers and to model a variety of other national economic impacts. We tallied approximately $32 billion in direct sales across 590 license agreements. While the majority of license agreements with sales belong to smaller companies (which often attract additional investment), some large companies generate higher revenues. Further statistical modeling with the heavily anonymized data identifies features of license agreement situations that influence economic outcomes. Technology license agreements are a form of PPP that performs well against its goal of economic development without the downsides of some PPPs. Importantly, entrepreneurs can use this form of PPP to attract investment and to generate jobs and other societal benefits.